University students and racial discrimination: an analysis based on family income - Nazaré Oliveira, Eliany (2025)
Introduction: Racial discrimination is a complex problem that directly affects the experience of university students, impacting not only their academic performance, but also their mental health and well-being. Objective: To discuss the characteristics of racial discrimination and its interfaces with the family income of university students. Methodology: A descriptive, exploratory, cross-sectional study was conducted, with a sample of 751 university students from the state of Ceará, Brazil. The instruments used were a sociodemographic questionnaire and the discrimination experience scale. Results: Among the students, 36.9% had a family income of between 1 and 2 salaries.  With regard to discrimination because of their race or color, those with an income of less than one minimum wage were the ones who experienced this the most, 39.9%. The place of occurrence with the highest exposure for those with an income of less than one minimum wage was school, 37.5%. Conclusion: The results suggest that there is a direct relationship between family income and racial discrimination: the lower the income, the greater the exposure to racial discrimination. There is an urgent need to implement strategies to protect and support those who experience racial discrimination.